Tourette syndrome. The importance of the prevailing attitude and the social problems of the sufferers: literature review - B. Puzonaitë; A. Vaitkus (Neurologijos seminarai)
Background. Tourette syndrome (TS) is not often encountered in the practice of doctors. Biased opinions of the public and doctors prevail about TS, its symptoms are often misunderstood or not recognized in time. This can lead to the development of social problems and stigmatization of the sufferers. Therefore, it is extremely important to rely on scientific research data in order to get a correct understanding of the TS itself and the possible consequences of its misinterpretation for the further social life of children.